Invasive aspergillosis due to Aspergillus cryptic species: A prospective multicentre study. Issue 11 (11th July 2021) - Imbert, Sebastien; Cassaing, Sophie; Bonnal, Christine; Normand, Anne‐Cecile; Gabriel, Frederic; Costa, Damien; Blaize, Marion; Lachaud, Laurence; Hasseine, Lilia; Kristensen, Lise; Guitard, Juliette; Schuttler, Christine; et al.
Abstract: Objectives: Aspergillus cryptic species are increasingly recognised causes of Aspergillus diseases, including life‐threatening invasive aspergillosis (IA). However, as their accurate identification remains challenging in a routine practice, few is known from a clinical and epidemiological perspective. Recently, the MSI application has emerged as a powerful tool for the detection and identification of Aspergillus cryptic species. We aimed to use to the network of users of the MSI application to conduct a multicentre prospective screening of Aspergillus cryptic species‐related IA and analyse their epidemiological, clinical and mycological characteristics. Methods: Over a 27‐month period, the clinical involvement of 369 Aspergillus cryptic isolates, from 13 French and Danish MSI application users, was prospectively analysed. Species identification was confirmed by DNA‐sequencing and antifungal susceptibility testing was performed using EUCAST reference method. Fifty‐one A fumigatus sensu stricto invasive cases were also analysed. Results: Fifteen cryptic isolates were responsible of IA. Eight species were involved, including 5 cases related to the species A sublatus . These species showed high rate of in vitro low susceptibility to antifungal drugs. In comparison with A fumigatus sensu stricto invasive cases, pre‐exposure to azole drugs was significantly associated with cryptic IA ( P = .02). Discussion: This study brings new insights in cryptic species related IA and underlines the importance to identify accurately at the species level these Aspergillus isolates. The increasing use of antifungal drugs might lead in the future to an epidemiologic shift with an emergence of resistant isolates involved in IA.